AN INTRODUCTION TO THE ART OF MASSAGE - P.R, *Rajalekshmy; Sreedhar, Cijith (AYUSHDHARA, 2016)
Massage, or systematic rubbing and manipulation of the tissues of the body, is probably one of the oldest of all means used for the relief of bodily infirmities. There are various evidences for the practice of massage in different forms in medieval times also. Later on, Dr. Mezger and Kellogg developed the two types of massage viz, Swedish and Kellogg massage. The basic movements and procedures are the same in both. The four major procedures in Swedish massage are effleurage (stroking), frictions, petrissage (kneading) and tapotement (percussion). Swedish massage is not much popular in India but it is widely practiced in other countries. The practice of massage produces mechanical, reflex and metabolic effects in the body. Massage influences the circulation, respiratory activities, nervous coordination and digestive activities which are detailed in the paper. Massage helps in lymph and blood circulation and absorption of waste and effused products. Massage can be indicated in arthritic pain, paralysis etc. and contra indicated in skin diseases, fever, after surgery etc. Care should be taken to make all the movements from wrist otherwise it generates pain. Only few studies have been conducted on massage and its effects. Moreover not much authentic books are available on massage except Kellog’s ‘The Art of Massage’. More and more studies should be done in order to make the practice of massage popular.